MODIFIED EPOXY RESIN AND METHOD FOR PRODUCING SAME, RESIN COMPOSITION, CURED PRODUCT, etc., AND DECOMPOSITON METHOD
Patent Information
- Application Number
- KR1020260036010
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-02-28
- Filing Date
- 2026-02-26
- Publication Date
- 2026-09-04
Smart Images

Figure PAT00022_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a modified epoxy resin having low viscosity and providing a cured product having excellent degradability and mechanical strength. Furthermore, the invention relates to a resin composition having the modified epoxy resin as an essential component and the cured product thereof. Background Technology
[0002] Epoxy resins are widely used in fields such as paints, civil engineering, adhesives, and electrical materials due to their excellent heat resistance, adhesion, chemical resistance, water resistance, mechanical strength, and electrical properties.
[0003] On the other hand, cured products obtained by curing thermosetting resins, including epoxy resins, are insoluble in solvents and do not dissolve even at high temperatures (infusible). Consequently, they lack recyclability and reusability, and since the cured product becomes waste after use, reducing waste and mitigating the environmental burden remains a challenge. Additionally, due to their high adhesive performance, there is also the challenge of limited disassembly and reusability after use. Therefore, cured products using thermosetting resins require waste reduction and reusability, and imparting biodegradability is considered an effective solution for this.
[0004] Against this backdrop, Patent Document 1 discloses a method of decomposing a cured product by first incorporating a carbonate structure having solution decomposition properties into a thermosetting resin, curing the product, and then immersing it in a specific solution to break the bonds. However, the epoxy resin disclosed in Patent Document 1 has high viscosity, which limits its applications. Prior art literature
[0005] Japanese Patent No. 7555376 The problem to be solved
[0006] Accordingly, the problem to be solved by the present invention is to provide a cured product having excellent degradability and mechanical strength, and to provide a low-viscosity modified epoxy resin, a resin composition, and a cured product thereof that is useful for applications such as lamination, molding, casting, and bonding. means of solving the problem
[0007] In order to solve the above problem, the inventors carefully examined various structures of difunctional epoxy resins and discovered that a modified epoxy resin having a specific structure has low viscosity and that a cured product obtained by curing the resin composition has excellent degradability and mechanical strength, thereby completing the present invention.
[0008] That is, the present invention is a modified epoxy resin characterized by the following general formula (1).
[0009] [Chemical Formula 1]
[0010]
[0011] Here, X is a monovalent group represented by the above formula (2-1) or the above formula (2-2), and the above formula (2-1) and the above formula (2-2) may be mixed within one molecule. Y is a divalent group and has at least a dicyclic hydrocarbon group that may have heteroatoms. n 1 n is the average value of the number of repetitions, and is between 0 and 500 inclusive. 1 If this is 0, X has at least the group represented by Equation (2-2). n 2 is the average value of the number of repetitions, and is between 0 and 6 inclusive.
[0012] In formula (1), Y is a divalent group and it is preferable to have at least 10 mass% of a carbon alicyclic hydrocarbon group having 1 to 15 carbon atoms that may have an oxygen atom.
[0013] In formula (1), Y is a divalent group, and it is preferable to have at least 10 mass% of the divalent group represented by the following formula (3-1) and / or the following formula (3-2).
[0014] [Chemical Formula 2]
[0015]
[0016] In addition, the present invention is a resin composition comprising the modified epoxy resin and a curing agent.
[0017] Furthermore, the present invention comprises a cured product formed by curing the resin composition, a prepreg formed by the resin composition or its semi-cured product and a fibrous substrate, and a resin sheet formed by the resin composition or its semi-cured product and a support film. Additionally, the present invention comprises a laminated plate formed by laminating the prepreg and / or the resin sheet. Furthermore, the present invention comprises a resin composition for a fiber-reinforced composite material characterized by impregnating a reinforcing fiber with the resin composition, and a fiber-reinforced composite material obtained from the resin composition for a fiber-reinforced composite material.
[0018] In addition, the present invention is a method for manufacturing the modified epoxy resin, characterized by reacting a difunctional epoxy resin represented by the following general formula (4) with a diphenyl carbonate represented by the following formula (5).
[0019] [Chemical Formula 3]
[0020]
[0021] Here, Y has the same meaning as in general formula (1). G is a 1-value group represented by the above formula (2-1). n 2 is the average value of the number of repetitions, and is between 0 and 6 inclusive.
[0022] In addition, the present invention is a method for decomposing the cured material, laminate, or fiber-reinforced composite material, characterized by reacting the cured material, laminate, or fiber-reinforced composite material with a primary amine. Effects of the invention
[0023] According to the present invention, a cured product having excellent degradability and mechanical strength, and a modified epoxy resin and a resin composition having low viscosity can be provided. This modified epoxy resin has excellent degradability, mechanical strength, and viscosity, and can be preferably used in composite materials such as fiber-reinforced plastics (FRP) where degradability and mechanical strength are required, laminates, adhesives such as film adhesives and liquid adhesives. Brief explanation of the drawing
[0024] Figure 1 is a GPC chart of the modified epoxy resin of Example 1. Figure 2 is an IR chart of the modified epoxy resin of Example 1. Specific details for implementing the invention
[0025] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments and examples, but may be implemented with arbitrary modifications within the scope of the claims of the present invention and their equivalents without departing from the scope of the claims and equivalents thereof.
[0026] The modified epoxy resin of the present invention is a modified epoxy resin characterized by being represented by the general formula (1), and has a structure represented by formula (2-1) or formula (2-2). Formulas (2-1) and (2-2) may be mixed within one molecule. In addition, it has at least a divalent hydrocarbon group that may have a heterovalent element.
[0027] [Chemical Formula 4]
[0028]
[0029] The weight average molecular weight (Mw) of the modified epoxy resin of the present invention is preferably 250 or more and 100,000 or less. Here, if Mw is less than 250, the introduction of structures that improve degradability is likely to be reduced. If Mw is greater than 100,000, compatibility may decrease or handling of the resin may become difficult. Furthermore, from the perspective of improving the degradability of the modified epoxy resin, Mw is more preferably 300 or more. From the perspective of improving handling, Mw is more preferably 90,000 or less, and even more preferably 80,000 or less. For applications such as impregnation into a substrate, Mw is preferably 10,000 or less, and more preferably 5,000 or less. In addition, the Mw of the modified epoxy resin can be measured by the gel permeation chromatography method (GPC method) described in the examples.
[0030] If the epoxy equivalent of the modified epoxy resin is 150 to 100,000 g / eq., it is possible for the modified epoxy resin to participate in the curing reaction and be incorporated into the cross-linked structure, so it is desirable to have this range. The epoxy equivalent is more preferably 150 to 40,000 g / eq., and even more preferably 200 to 20,000 g / eq. For film applications, since film-forming properties are required, it is desirable for the epoxy equivalent to be higher, preferably 5,000 to 50,000 g / eq., more preferably 10,000 to 50,000 g / eq., and even more preferably 20,000 to 50,000 g / eq. Meanwhile, for applications where it is impregnated into a substrate, good impregnation properties are required, so the epoxy equivalent is preferably low, preferably 150 to 10,000 g / eq., more preferably 150 to 5,000 g / eq., and even more preferably 150 to 3,000 g / eq.
[0031] In the above general formula (1), n 1n is the number of repetitions and is the average value. The range of the value is from 0 to 500. From the perspective of moldability and handling properties, it is preferably from 0 to 200, more preferably from 0 to 100, and even more preferably from 0 to 50. Number of repetitions n 1 It can be calculated from the number-average molecular weight (Mn) obtained by the GPC method. 1 In the case where this is 0, X has at least the group of Equation (2-2) above. Also, n 2 is the average value of the number of repetitions, and is 0 to 6, and preferably 0 to 3.
[0032] In the above general formula (1), Y is a divalent group and has at least a dicyclic hydrocarbon group that may have heteroatoms.
[0033] As a divalent group and an alicyclic hydrocarbon group having a heteroatom, for example, aziridine, oxirane, thiran, azetidine, 1,3-diazetidine, oxetane, thiethane, β-lactam, pyrrolidine, pyrazolidine, imidazolidine, tetrahydrofuran, 1,3-dioxolane, tetrahydrothiophene, 1,2-oxathiolan, 1,3-oxathiolan, sulfolane, thiazolidinedione, succinimide, 2-oxazolidone, hydantoin, piperidine, piperazine, tetrahydropyran, 1,4-dioxane, thian, 1,3-dithian, 1,4-dithian, 1,3,5-thritian, morpholine, thiomorpholine, thiomorpholine dioxide, Pyrrolizidine, decahydroisoquinoline, decahydroquinoline, quinuclidein, 1-azadamantan, 2-azadamantan, oxephan, azocan, thiocan, azonan, 1-oxaspiro[4.5]decane, 1,6-oxaspiro[3.4]octane, 1-oxaspiro[4.4]nonan-2-one, 2-oxa-7-azspiro[3.5]nonan, 1,4-dioxa-7-azspiro[4.4]nonan, 1,3-diazaspiro[4.4]non-2-en-4-one, 2,9-diazaspiro[5.5]undecan-1-one, 8-azspiro[4.5]decane-7,9-dione, Examples include divalent groups containing structures such as 1,3,8-triazaspiro[4.5]decane-4-one, 1,4-dithia-7-azaspiro[4.4]nonane, 2,4,8,10-tetraoxaspiro[5.5]undecane, 3,9-bis(1,1-dimethylethyl), and 1,4:3,6-dianhydro-2,5-dideoxyhexitol. These structures may be substituted with substituents.
[0034] Examples of divalent groups and alicyclic hydrocarbon groups that do not have heteroatoms include, for instance, divalent groups including structures such as cyclopropane, cyclobutane, cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclodecane, cycloundecane, cyclododecane, bicycloundecane, decahydronaphthalene, cubene, basketane, hausene, dimethylcyclohexane, bicyclohexyl, dicyclohexylmethane, and 2,2-dicyclohexylpropane in cycloalkanes. These structures may be substituted with substituents.
[0035] In the above general formula (1), Y may have a backbone derived from the remaining backbone of a difunctional epoxy resin (diglycidyl ether compound) excluding two glycidyloxy groups. Examples of difunctional epoxy resins include bisphenol-type epoxy resins such as bisphenol A-type epoxy resin, bisphenol F-type epoxy resin, bisphenol acetophenone-type epoxy resin, and diphenyl ether-type epoxy resin, as well as biphenol-type epoxy resin, diphenyl dicyclopentadiene-type epoxy resin, alkylene glycol-type epoxy resin, and aliphatic cyclic epoxy resin. These epoxy resins may be substituted with substituents. When calculated from the injection weight ratio of the raw material, Y has at least a divalent group and may have an alicyclic hydrocarbon group that may have a heteroatom. From the perspective of improving handling, it is desirable to have at least 10 mass% of a dicyclic hydrocarbon group that is a divalent group and may have heteroatoms as Y, calculated from the injection weight ratio of the raw material. More preferably, it is 30 mass% or more, even more preferably 40 mass% or more, and even more preferably 50 mass% or more. Accordingly, by having a suitable amount of a framework derived from a difunctional epoxy resin in the modified epoxy resin of the present invention, fine adjustment of solvent solubility, degradability, mechanical properties, adhesion, viscosity, etc., can be made.
[0036] Among these, from the perspective of decompositionability, viscosity, etc., it is preferable to have at least 10 mass% of a carbon alicyclic hydrocarbon group having 1 to 15 carbon atoms that may have oxygen atoms as a heterocyclic hydrocarbon group that may have the above-mentioned heterocyclic elements. A more preferable Y group is to have at least 10 mass% of a divalent group represented by the following formula (3-1) and / or the following formula (3-2), and it is even more preferable to have a divalent group represented by the following formula (3-1).
[0037] [Chemical Formula 5]
[0038]
[0039] In general formula (1), the terminal group X is a monovalent group represented by formula (2-1) or formula (2-2), and formulas (2-1) and (2-2) may be mixed within one molecule. Preferably, it has at least the group represented by formula (2-2). In the raw material epoxy resin of general formula (4), the terminal group is the glycidyl group of formula (2-1), denoted as G in total amount, whereas in the modified epoxy resin of general formula (1), when reacted with diphenyl carbonate and calculated from the injection weight ratio of the raw material, at least 25 mass% of the terminal groups is preferably the group represented by formula (2-2). Among the terminal groups, the group represented by formula (2-2) is more preferably at least 50 mass%. As a modified epoxy resin, it is calculated as a molar% of the same amount as the mass%.
[0040] Also, the carbonate concentration of the carbonate structure containing the group represented by the formula (2-2) is the terminal group X and the repeating unit n in the above formula (1). 1 As a total, it is preferably 0.05 to 0.20 eq. / 100g, more preferably 0.07 to 0.17 eq. / 100g, and even more preferably 0.08 to 0.15 eq. / 100g. When the carbonate concentration is within this range, the degradability, viscosity, etc. are excellent.
[0041] [Chemical Formula 6]
[0042]
[0043] The modified epoxy resin of the present invention is one that imparts decomposition properties without significantly increasing viscosity during modification, and a preferred manufacturing method is a method of reacting a difunctional epoxy resin represented by general formula (4) with a diphenyl carbonate represented by formula (5).
[0044] [Chemical Formula 7]
[0045]
[0046] In Equation (4), Y is the same as in Equation (1). G is the 1-value group represented by Equation (2-1) above. n 2 is the average value of the number of repetitions, and is 0 to 6, and preferably 0 to 3.
[0047] In this manufacturing method, the reaction between the epoxy resin of formula (4) and the diphenyl carbonate of formula (5) is considered to be a mechanism in which the diphenyl carbonate is phenol dissociated and undergoes a polycondensation reaction with the epoxy group, rather than the secondary hydroxyl group, with respect to the epoxy resin.
[0048] The difunctional epoxy resin used in the present invention is an epoxy resin represented by the formula (4) above, and examples include an epoxy resin obtained by reacting a difunctional phenol compound represented by HO-Y-OH with an epihalohydrin in the presence of an alkali metal compound. In the difunctional phenol compound HO-Y-OH, Y is the same as Y in the formula (4) above.
[0049] The raw material epoxy resin represented by formula (4) has an epoxy equivalent weight preferably of 100 to 400 g / eq., more preferably of 100 to 250 g / eq.
[0050] Examples of epihalohydrins include epichlorohydrin and epibromohydrin.
[0051] Examples of alkali metal compounds include alkali metal hydroxides such as sodium hydroxide, lithium hydroxide, and potassium hydroxide; alkali metal salts such as sodium carbonate, sodium bicarbonate, sodium chloride, lithium chloride, and potassium chloride; alkali metal alkoxides such as sodium methoxide and sodium ethoxide; alkali metal salts of organic acids such as sodium acetate and sodium stearate; alkali metal phenoxides; sodium hydride; and lithium hydride. The amount used is 0.80 to 1.20 molar, preferably 0.85 to 1.05 molar, relative to the functional group (hydroxyl group) in the above-mentioned difunctional phenol compound. If the amount is less than this, the amount of residual hydrolyzable chlorine may increase. The alkali metal compound is used in an aqueous solution, an alcohol solution, or a solid state.
[0052] In the epoxidation reaction, an excess amount of epihalohydrin is used for difunctional phenol compounds. Typically, 1.5 to 15 times the mole of epihalohydrin is used per 1 mole of functional groups in the difunctional phenol compound, but preferably 2 to 10 times the mole, and more preferably 5 to 8 times the mole. If the amount is greater than this, production efficiency is likely to decrease, and if the amount is less than this, the production of high molecular weight epoxy resin is likely to increase.
[0053] The epoxidation reaction is typically carried out at a temperature of 120°C or lower. When the temperature is high during the reaction, the amount of so-called difficult-to-hydrolyze chlorine increases, making it difficult to achieve high purity. Preferably, the temperature is 100°C or lower, and more preferably, 85°C or lower.
[0054] In the difunctional epoxy resin of formula (4) obtained, the number of repetitions n as described above 2is the average value of the number of repetitions, and is 0 to 6, preferably 0 to 3, more preferably 0 to 1, and even more preferably 0 to 0.5. In the difunctional epoxy resin of Formula (4) obtained by reacting the above difunctional phenol compound with an epihalohydrin, the number of repetitions n 2 It is typical for n to become greater than 0. 2 In order to make it 0, there is a method of highly purifying the epoxy resin prepared by a known method by means of distillation, crystallization, etc., or by allylating the above-mentioned difunctional phenolic compound and then epoxidizing it by oxidizing the olefin portion.
[0055] The difunctional epoxy resin represented by Formula (4) used as a raw material is not limited to those having at least the aforementioned Y group, but examples include cyclohexanedimethanol diglycidyl ether, cyclohexanediol diglycidyl ether, isosorbide diglycidyl ether, isomandide diglycidyl ether, hydrogenated bisphenol A type epoxy resin, hydrogenated bisphenol F type epoxy resin, hydrogenated biphenol type epoxy resin, 2,4,8,10-tetraoxasspiro[5.5]undecane, 3,9-bis[1,1-dimethyl-2(2-oxyranylmethoxy)ethyl], etc. As long as the difunctional epoxy resin represented by Formula (4) contains any of these, other difunctional epoxy resins other than it may be used in combination. Other difunctional epoxy resins that may be used in combination include, for example, bisphenol-type epoxy resins such as bisphenol A-type epoxy resin, bisphenol F-type epoxy resin, bisphenol acetophenone-type epoxy resin, and diphenyl ether-type epoxy resin, biphenol-type epoxy resin, diphenyl dicyclopentadiene-type epoxy resin, alkylene glycol-type epoxy resin, and aliphatic ring-type epoxy resin, but are not limited to these. In the case of using a difunctional epoxy resin as a raw material, when a difunctional epoxy resin represented by formula (4) and other difunctional epoxy resins other than that are used in combination, it is preferable to use the difunctional epoxy resin represented by formula (4) in a ratio of at least 10 mass%. More preferably, it is at least 30 mass%, even more preferably at least 40 mass%, and even more preferably at least 50 mass%.
[0056] The number of repetitions n in Equation (4) 2 By using an epoxy resin having a value of 0 as a raw material, the modified epoxy resin of the present invention does not contain secondary hydroxyl groups, thereby further improving viscosity and moisture resistance. Meanwhile, for example, when fine-tuning adhesion to metal, a suitable number of repetitions n greater than 0 2By using the epoxy resin, a suitable amount of secondary hydroxyl groups may be present in the modified epoxy resin of the present invention within a range that does not significantly affect other physical properties such as viscosity and moisture resistance.
[0057] In the reaction between the difunctional epoxy resin represented by general formula (4) and the diphenyl carbonate represented by formula (5), one molecule of diphenyl carbonate reacts with two epoxy groups (one molecule of epoxy resin) of the difunctional epoxy resin to form a straight-chain polycondensation. Therefore, although the amount of raw material used needs to be appropriately adjusted according to the epoxy equivalent of the desired modified epoxy resin, it is preferable to use a range of 0.8 to 5 moles of the epoxy resin of formula (4) for every 1 mole of diphenyl carbonate of formula (5), i.e., a range of difunctional epoxy resin / diphenyl carbonate (molar ratio) of 0.8 to 5. More preferably, the range is 0.9 to 4 moles of diphenyl carbonate and a difunctional epoxy resin / diphenyl carbonate (molar ratio) of 0.9 to 4. In addition, it is also possible to substitute a portion of the compound represented by general formula (5) with the above difunctional phenol compound. Accordingly, as described above, fine adjustments such as solvent solubility, viscosity, and adhesion can be made by daring to have an appropriate amount of secondary hydroxyl groups present in the modified epoxy resin of the present invention.
[0058] In the manufacturing method, it is preferable to use a catalyst, and as the catalyst, it is preferable that the diphenyl carbonate of formula (5) be a compound having catalytic ability to preferentially react with the epoxy group rather than the secondary hydroxyl group of the epoxy resin. A basic compound is preferred, and examples include tertiary amines, cyclic amines, imidazole compounds, organic phosphorus compounds, quaternary ammonium salts, etc. In addition, these catalysts may be used alone or in combination of two or more types.
[0059] The amount of catalyst used is typically 0.001 to 1 mass% of the reaction solids, but when these compounds are used as catalysts, there is a risk that these catalysts will remain as residues in the resulting modified epoxy resin and shorten the pot life of the composition; therefore, the content of catalyst-derived nitrogen in the modified epoxy resin is preferably 0.5 mass% or less, and more preferably 0.3 mass% or less. In addition, the content of catalyst-derived phosphorus in the modified epoxy resin is preferably 0.5 mass% or less, and more preferably 0.3 mass% or less.
[0060] In the manufacturing method of the present invention, a reaction solvent may be used, and the solvent may be any solvent capable of dissolving the modified epoxy resin. Examples include aromatic solvents, ketone solvents, amide solvents, glycol ether solvents, ester solvents, etc. Furthermore, these solvents may be used as a single type or in combination of two or more types.
[0061] In the manufacturing method, the solid content concentration during the reaction is preferably 35 to 100 mass%. More preferably, it is 50 to 100 mass%, and even more preferably, 70 to 100 mass%. Additionally, if a high-viscosity product is formed during the reaction, the reaction may be continued by adding an additional solvent. After the reaction is finished, the solvent may be removed as needed, or it may be added.
[0062] The reaction temperature is carried out within a temperature range such that the catalyst to be used does not decompose. If the reaction temperature is excessively high, there is a risk that the catalyst will decompose, causing the reaction to stop, or that the resulting modified epoxy resin will deteriorate. If the reaction temperature is excessively low, there is a risk that the reaction will not proceed sufficiently and the desired molecular weight will not be achieved. Therefore, the reaction temperature is preferably 50 to 230°C, more preferably 70 to 210°C, even more preferably 90 to 200°C, and particularly preferably 100°C to 180°C. In addition, the reaction time is typically 1 to 12 hours, preferably 3 to 10 hours. When using low-boiling point solvents such as acetone or methyl ethyl ketone, the reaction temperature can be secured by carrying out the reaction under high pressure using an autoclave. Furthermore, if the removal of reaction heat is required, it is typically carried out by evaporation, condensation, or reflux of the solvent used due to the reaction heat, indirect cooling, or a combination of these methods.
[0063] The resin composition of the present invention is a resin composition comprising at least the modified epoxy resin of the present invention and a curing agent. In addition, the resin composition of the present invention may appropriately incorporate various additives, such as other epoxy resins described below, inorganic fillers, coupling agents, and antioxidants, as needed. The resin composition of the present invention provides a cured product that sufficiently satisfies all physical properties required for various applications.
[0064] In the present invention, a curing agent refers to a substance that contributes to a cross-linking reaction with a modified epoxy resin. Furthermore, in the present invention, even if a substance is commonly referred to as a curing accelerator, if it contributes to a cross-linking reaction with an epoxy resin, it is considered a curing agent.
[0065] The content of the curing agent in the resin composition of the present invention is preferably 0.1 to 150 parts by mass of the curing agent per 100 parts by mass of the modified epoxy resin (if other epoxy resins are included, all epoxy resins including those epoxy resins). More preferably, it is 2 to 130 parts by mass. In addition, the amount of non-volatile matter (solid matter) in the resin composition.
[0066] In the resin composition of the present invention, when other epoxy resins are included, the modified epoxy resin of the present invention is preferably 1 to 99 mass% of the total epoxy resin, and as a lower limit, more preferably 50 mass% or more, and even more preferably 80 mass% or more.
[0067] In the present invention, the term "solid component" refers to a component excluding the solvent, and includes not only solid modified epoxy resins or other epoxy resins, but also semi-solid or viscous liquids. Furthermore, the term "resin component" refers to the sum of the modified epoxy resin of the present invention and other epoxy resins.
[0068] There are no particular limitations on the curing agent used in the resin composition of the present invention, and any curing agent generally known as a curing agent for epoxy resins may be used. Preferred agents from the perspective of increasing heat resistance include phenolic resins, amine-based compounds, amide-based compounds, imidazole-based compounds, active ester-based curing agents, acid anhydride-based curing agents, etc. These curing agents may be used alone or in combination of two or more types.
[0069] Examples of other curing agents include acrylic acid ester resins, melamine resins, urea resins, cationic polymers, tertiary amines, organic phosphines, phosphonium salts, tetraphenyl boron salts, organic acid dihydrazides, boron halide complexes, polymercaptan-based curing agents, isocyanate compounds, polyisocyanate compounds, block isocyanate compounds, carbodiimide compounds, etc. These other curing agents may be used as a single type, or two or more types may be mixed in any combination and ratio.
[0070] The resin composition of the present invention may include epoxy resins other than the modified epoxy resin of the present invention. By using other epoxy resins, it is possible to supplement deficient physical properties or improve various physical properties. As for the epoxy resin, it is preferable that it has two or more epoxy groups within its molecule, and an epoxy resin having three or more epoxy groups is more preferable. Examples include polyglycidyl ether compounds, polyglycidylamine compounds, polyglycidyl ester compounds, alicyclic epoxy compounds, and other modified epoxy resins. These epoxy resins may be used alone, two or more types of epoxy resins of the same class may be used in combination, or epoxy resins of different classes may be used in combination.
[0071] In the resin composition of the present invention, a solvent or a reactive diluent may be added to appropriately adjust the viscosity of the resin composition during handling when forming a coating film. In the resin composition of the present invention, the solvent or reactive diluent is used to ensure the handling and workability during the molding of the resin composition, and there is no particular limitation on the amount used. Furthermore, in the present invention, the terms "solvent" and "solvent" as described above are distinguished according to their usage forms, but they may each be of the same type or different types.
[0072] Examples of solvents that may be included in the resin composition of the present invention include ketones such as acetone, methyl ethyl ketone (MEK), methyl isobutyl ketone, and cyclohexanone; esters such as ethyl acetate; ethers such as ethylene glycol monomethyl ether; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; alcohols such as methanol and ethanol; alkanes such as hexane and cyclohexane; and aromatics such as toluene and xylene. The solvents listed above may be used as a single type, or two or more types may be mixed in any combination and ratio.
[0073] Examples of reactive diluents include monofunctional glycidyl ethers such as allylglycidyl ether, difunctional glycidyl ethers such as propylene glycol diglycidyl ether, polyfunctional glycidyl ethers such as trimethylolpropane polyglycidyl ether, glycidyl esters, and glycidylamines.
[0074] These solvents or reactive diluents are preferably used in a non-volatile content of 90 mass% or less, particularly in the range of 20 to 80 mass%, and the appropriate type or amount is selected according to the application. For example, for printed circuit board applications, it is preferable to use polar solvents with a boiling point of 160 °C or lower, such as methyl ethyl ketone, acetone, or 1-methoxy-2-propanol, and the amount used is preferably 40 to 80 mass% as the non-volatile content. In addition, for adhesive film applications, it is preferable to use, for example, ketones, acetic acid esters, carbitols, aromatic hydrocarbons, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, etc., and the amount used is preferably 30 to 60 mass% as the non-volatile content.
[0075] In the resin composition of the present invention, a curing accelerator or a catalyst may be used as needed. Examples of curing accelerators or catalysts include imidazole-based compounds, phosphate compounds such as tertiary amines and phosphines, metal compounds, Lewis acids, amine complex salts, etc. These may be used alone or in combination of two or more types.
[0076] The amount of curing accelerator or catalyst can be appropriately selected according to the purpose of use, but 0.01 to 15 parts by mass are used as needed per 100 parts by mass of the epoxy resin component (all epoxy resin components including the modified epoxy resin of the present invention) in the resin composition. Preferably, 0.01 to 10 parts by mass, more preferably 0.05 to 8 parts by mass, even more preferably 0.1 to 5 parts by mass, and particularly preferably 0.1 to 1.0 parts by mass. By using a curing accelerator or catalyst, the curing temperature can be lowered or the curing time can be shortened.
[0077] In the resin composition of the present invention, various known flame retardants may be used within a range that does not reduce reliability, for the purpose of improving the flame retardancy of the resulting cured product. Examples of flame retardants that can be used include halogen-based flame retardants, phosphorus-based flame retardants, nitrogen-based flame retardants, silicone-based flame retardants, inorganic flame retardants, organometallic salt-based flame retardants, etc. From an environmental perspective, flame retardants that do not contain halogen are preferred, and phosphorus-based flame retardants are particularly preferred. These flame retardants may be used alone, two or more types of flame retardants of the same type may be used in combination, or flame retardants of different types may be used in combination.
[0078] The resin composition of the present invention may include components other than those described above for the purpose of further enhancing its functionality. Examples of such other components include fillers, thermoplastic resins, thermosetting resins, photocurable resins, UV inhibitors, antioxidants, coupling agents, plasticizers, fluxes, thixotropic agents, leveling agents, coloring agents, pigments, dispersants, emulsifiers, low-elastomers, release agents, defoaming agents, ion trapping agents, etc.
[0079] The resin composition of the present invention is obtained by uniformly mixing each of the above components. A resin composition comprising a modified epoxy resin, a curing agent, and, if necessary, various other components can be easily cured into a product using the same method known in the prior art. This cured product exhibits excellent degradability and mechanical properties, as well as good curing properties. The term "curing" as used herein refers to intentionally curing the resin composition by heat and / or light, and the degree of curing can be controlled according to the desired properties and applications. The degree of progress may be fully cured or semi-cured and is not particularly limited, but the reaction rate of the curing reaction between the epoxy group and the curing agent is typically 5 to 95%.
[0080] The resin composition of the present invention can be cured in the same manner as a known epoxy resin composition to obtain a cured product. As a method for obtaining a cured product, the same method as that used for a known epoxy resin composition may be adopted, and methods such as molding, injection, potting, dipping, drip coating, transfer molding, compression molding, etc., or forming the product into a resin sheet, a copper foil attached to the resin, prepreg, etc., and laminating it to form a laminated board by heating and pressurizing, are suitably used. At that time, the curing temperature is typically in the range of 80 to 300°C, and the curing time is typically about 10 to 500 minutes. For example, this heating is preferably carried out as a two-stage process consisting of a first heating step of 10 to 150 minutes at 80 to 180°C and a second heating step of 60 to 300 minutes at 120 to 200°C. Furthermore, for formulations where the glass transition temperature (Tg) exceeds the temperature of the second heating step, it is preferable to additionally carry out a third heating step of 60 to 120 minutes at 150 to 280°C. By carrying out such second and third heating steps, curing defects can be reduced. When manufacturing resin semi-materials such as resin sheets, resin-attached copper foil, and prepregs, the curing reaction of the resin composition is typically advanced by heating or the like to the extent that the shape can be maintained. In cases where the resin composition contains a solvent, most of the solvent is typically removed by methods such as heating, reduced pressure, or air drying, but 5 mass% or less of the solvent may be left in the resin semi-finished product.
[0081] A prepreg obtained using the resin composition of the present invention will be described. The prepreg of the present invention consists of the resin composition or its semi-cured material and a fibrous substrate. As the fibrous substrate, woven or nonwoven fabrics of inorganic fibers such as carbon fibers or glass, or organic fibers such as polyester, polyamine, polyacrylic, polyimide, Kevlar, or cellulose may be used, but are not limited thereto. The method for manufacturing the prepreg from the resin composition and the fibrous substrate of the present invention is not particularly limited; for example, the substrate may be impregnated by immersing it in a resin varnish in which the resin composition has its viscosity adjusted with a solvent, and then heat-drying it to semi-cure (B-stage) the resin component. For example, it may be heat-dried at 100 to 200°C for 1 to 40 minutes. Here, it is preferable that the resin content in the prepreg be 30 to 80 mass%.
[0082] A resin sheet obtained using the resin composition of the present invention will be described. The resin sheet of the present invention consists of the resin composition or a semi-finished product thereof and a support film. As the support film, polyolefins such as polyethylene, polypropylene, and polyvinyl chloride, polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate, polycarbonates, polyimides, and furthermore, metal foils such as release paper, copper foil, and aluminum foil may be used, but are not limited thereto. The thickness of the support film is not particularly limited, but is typically 10 to 150 μm, and preferably used in the range of 25 to 50 μm. The method for manufacturing the resin sheet from the resin composition and the support film of the present invention is not particularly limited, and for example, a method may be used in which the resin composition is applied to the support film in a resin varnish whose viscosity is adjusted with an aromatic or ketone-based solvent, and then dried. It is obtained by heating and drying to semi-cure (B-stage) the resin component, and, for example, can be heated and dried at 100 to 200°C for 1 to 40 minutes. Here, the amount of resin in the resin sheet is preferably 30 to 80 mass% of the resin content. In addition, the thickness of the resin component is not particularly limited, but is in the range of 3 to 200 μm, more preferably 5 to 105 μm. The coating may be repeated multiple times as needed, and it is also possible to repeat the coating using multiple solutions with different compositions or concentrations to finally adjust the desired resin composition and amount of resin.
[0083] A method for manufacturing a laminate using the prepreg or resin sheet of the present invention is described. When forming a laminate using prepreg, for example, one or multiple sheets of prepreg are laminated, and a metal foil is placed on one or both sides to form a laminate, and this laminate is heated and pressed to integrate the laminates. Here, as the metal foil, a single, alloy, or composite metal foil such as copper, aluminum, brass, or nickel may be used. Regarding the conditions for heating and pressing the laminate, the heat and pressurization should be appropriately adjusted under conditions where the resin composition cures. If the amount of pressure applied is excessively low, air bubbles may remain inside the resulting laminate, which may lead to a deterioration of electrical properties. Therefore, it is desirable to apply pressure under conditions that satisfy moldability. For example, the temperature may be 160 to 220°C and the pressure 49 to 490 N / cm². 2 (5 ∼ 50 kgf / cm 2 ), and the heating time can be set to 10 to 240 minutes, respectively. A resin sheet may also be used instead of prepreg.
[0084] Furthermore, a multilayer plate can be manufactured using the single-layer laminate obtained in this way as an inner layer material. In this case, circuits are first formed on the laminate using methods such as the additive method or the subtractive method, and the surface of the formed circuits is treated with an acid solution to perform a blackening treatment, thereby obtaining an inner layer material. An insulating layer is formed using prepreg or a resin sheet on one or both circuit-formed surfaces of this inner layer material, and a conductive layer is formed on the surface of the insulating layer to form a multilayer plate.
[0085] When forming an insulating layer with a resin sheet, a laminate is formed by placing the resin sheet on the circuit-forming surface of a plurality of inner layer materials. Alternatively, a laminate is formed by placing the resin sheet between the circuit-forming surface of the inner layer material and a metal foil. Then, by integrally molding this laminate by heating and pressing, the cured resin sheet is formed as an insulating layer, and at the same time, a multilayer structure of the inner layer material is formed. Alternatively, the inner layer material and the metal foil, which is the conductor layer, are formed as insulating layers by using the cured resin sheet. Here, the same metal foil used in the laminated plate used as the inner layer material may be used.
[0086] In addition, heat-pressure molding can be performed under the same conditions as the molding of the inner layer material. When forming an insulating layer by applying a resin composition to a laminate, the resin composition is preferably applied to the circuit-forming surface resin of the outermost layer of the inner layer material to a thickness of 5 to 100 μm, and then heated and dried at 100 to 200°C for 1 to 90 minutes to form a sheet. This is formed by a method generally called the casting method. It is preferable to form a thickness of 5 to 80 μm after drying. On the surface of the multilayer laminate formed in this way, via holes or circuits can be formed using an additive method or a subtractive method to form a printed circuit board.
[0087] Furthermore, by repeating the above method using this printed circuit board as an inner layer material, it is possible to form an even more multi-layered laminate.
[0088] In addition, when forming an insulating layer with prepreg, one or more sheets of prepreg are laminated on the circuit forming surface of the inner layer material, and a metal foil is additionally placed on the outer side to form a laminate. Then, by heating and pressurizing this laminate to form an integral structure, the cured prepreg is formed as an insulating layer, and the metal foil on the outer side is formed as a conductor layer.
[0089] Here, the same metal foil used in the laminated board used as the inner layer material may be used. In addition, heat pressure molding may be performed under the same conditions as the molding of the inner layer material. On the surface of the multilayer laminated board formed in this way, via holes or circuits may be formed using an additive method or a subtractive method to form a printed circuit board.
[0090] Furthermore, by repeating the above method using this printed circuit board as an inner layer material, an even more multilayered multilayer board can be formed.
[0091] In addition, when the resin sheet of the present invention is used as a bonding sheet, for example, two substrates can be bonded together with the resin sheet. Each of the two substrates is, for example, a laminated board or a printed circuit board. Specifically, for example, a resin sheet is produced by forming an epoxy resin composition into a sheet shape on a support film by a coating method or the like, and then drying or semi-curing it by heating. This resin sheet is superimposed on a substrate (first substrate), and the support film is peeled off from the resin sheet to superimpose another substrate (second substrate). That is, the first substrate, the resin sheet (epoxy resin composition), and the second substrate are laminated in that order. Subsequently, by heating and curing, the first substrate and the second substrate are bonded together through the cured product of the epoxy resin composition.
[0092] The fiber-reinforced composite material of the present invention can be obtained by impregnating a reinforcing fiber with the resin composition of the present invention to obtain a composition for the fiber-reinforced composite material, and then molding and curing the same. Here, the reinforcing fiber may be any of the following: twisted yarn, untwisted yarn, or non-twisted yarn; however, untwisted yarn or non-twisted yarn is preferred because it has excellent moldability in the fiber-reinforced composite material. Furthermore, the form of the reinforcing fiber may be one in which the fiber direction is aligned in one direction or a woven fiber may be used. In the case of a woven fiber, it may be freely selected from plain weave, satin weave, etc., depending on the part or application used. Specifically, carbon fiber, glass fiber, aramid fiber, boron fiber, alumina fiber, silicon carbide fiber, etc., can be used because they have excellent mechanical strength and durability; these may be used alone or in combination of two or more types. Among these, carbon fibers are particularly desirable in that they improve the strength of the molded product, and various types of such carbon fibers can be used, including polyacrylonitrile-based, pitch-based, and rayon-based types.
[0093] A method for obtaining a fiber-reinforced composite material from the resin composition of the present invention is not particularly limited, but may include, for example, a method of uniformly mixing each component constituting the resin composition to produce a varnish, and impregnating a substrate such as a sheet formed by arranging continuous carbon fibers in one direction or a carbon fiber fabric as a prepreg, a method of placing a resin layer on at least one side of the surface of the carbon fiber substrate, a method of additionally placing a fiber layer on the said surface, a method of immersing unidirectional reinforcing fibers arranged side by side in one direction into the varnish obtained above (pre-curing state in the full-trusion method or filament winding method, tow prepreg), and a method of overlapping reinforcing fiber sheets or fabrics and setting them in a mold, and then injecting resin into the mold and applying pressure to impregnate or depressurizing the interior to impregnate (pre-curing state in the RTM method).
[0094] The fiber-reinforced composite material of the present invention preferably has a volume content of reinforcing fibers of 40% to 85% relative to the total volume of the molded article, and more preferably a range of 50% to 75% in terms of strength. If the volume content is less than 40%, the content of the resin composition is excessively high, and the elastic modulus or strength of the resulting cured product may be insufficient, or the required general characteristics may not be satisfied. Furthermore, if the volume content exceeds 85%, there is a lack of resin in the reinforcing fibers, which leads to insufficient adhesion or the occurrence of voids, and the elastic modulus or strength of the cured product may be insufficient, or interfacial adhesion may be reduced.
[0095] The cured product, laminate, or fiber-reinforced composite material obtained from the resin composition of the present invention has excellent degradability and mechanical properties.
[0096] The decomposition method of the present invention involves reacting the cured product, laminate, or fiber-reinforced composite material obtained above with a primary amine. It is believed that decomposition is promoted by using a primary amine, which causes the carbonate structure of the cured product, etc., to depolymerize. It is believed that because it has a cycloaliphatic hydrocarbon group, it has a lower molecular weight than general-purpose epoxy resins, and the concentration of the carbonate structure in the cured product involved in decomposition increases, making it easier to decompose.
[0097] In the decomposition method of the present invention, any primary amine may be used. Examples include methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, heptylamine, octylamine, nonylamine, ethylenediamine, hexamethylenediamine, spermidine, spermine, amantadine, aniline, toluidine, benzidine, catecholamine, phenethylamine, etc. Additionally, these compounds may be used as a single type or in combination of two or more types.
[0098] In the decomposition method, the reaction temperature is preferably 50 to 230 ℃, more preferably 70 to 200 ℃, and even more preferably 90 to 180 ℃. In addition, the reaction time is typically 0 to 24 hours, preferably 0 to 10 hours, and more preferably 0 to 4 hours.
[0099] Examples
[0100] The present invention will be explained in more detail below with reference to examples and comparative examples, but it is not limited thereto. Unless otherwise specified, “parts” indicates parts by mass, and “%” indicates % by mass. Additionally, analysis methods and measurement methods are shown below. Furthermore, the units of various equivalents are all “g / eq.”
[0101] (1) GPC Chart (Mw) :
[0102] It was obtained by GPC measurement. Specifically, the main body HLC8320GPC (manufactured by Tosoh Corporation) was used with a column (TSKgel A series configuration of SuperH-H, SuperH2000, SuperHM-H, and SuperHM-H (manufactured by Tosoh Corporation) was used, and the column temperature was set to 40 ℃. Additionally, tetrahydrofuran (THF) was used as the eluent, the flow rate was 1.0 mL / min, and a differential refractive index detector was used as the detector. For the measurement sample, 0.1 g of solid content was dissolved in 10 mL of THF and filtered through a 0.45 μm microfilter, and 50 μL of the resulting solution was used. The calibration curve was prepared using standard polystyrene (manufactured by Tosoh Corporation, PStQuick A, PStQuick B, and PStQuick C). Data processing was performed using the GPC8020 Model II Version 6.00 manufactured by Tosoh Corporation.
[0103] (2) IR (infrared absorption spectrum):
[0104] A Fourier transform infrared spectrophotometer (Perkin Elmer Precisely manufactured, Spectrum One FT-IR Spectrometer 1760X) was used, sodium chloride was used in the cell, and a sample dissolved in chloroform was applied to the cell and dried, then at a wavenumber of 500 to 4000 cm⁻¹ -1 The transmittance of was measured.
[0105] (3) Epoxy equivalent:
[0106] JIS Measurements were performed in accordance with K7236. Specifically, a potentiometric titration apparatus was used, chloroform was used as the solvent, a tetraethylammonium bromide acetic acid solution was added, and a 0.1 mol / L perchloric acid-acetic acid solution was used.
[0107] (4) Melt viscosity :
[0108] The viscosity at 150°C was measured using an ICI viscosity measuring device (manufactured by Toa Industrial Co., Ltd., CV-1S).
[0109] (5) Bending modulus:
[0110] Measurements were taken using the 3-point bending test (Method A) according to the JIS K7074 standard. The testing machine used was the Autograph AGS-X manufactured by Shimadzu Science, and the dimensions of the sample were set to a thickness of 2 mm, a length of 100 mm, and a width of 15 mm, and the test was conducted at a test speed of 2 mm / min.
[0111] (6) Decomposition time :
[0112] In a four-necked glass separable flask equipped with a stirring device, a thermometer, a cooling tube, and a nitrogen gas introduction device, 100 parts of a cured product with a thickness of 2 mm, a length of 1 cm, and a width of 1 cm at room temperature and 4000 parts of 1-hexylamine were injected, and the temperature was raised to 125 ℃ while stirring with nitrogen gas flow, and stirring was continued, and the time until the cured product disappeared visually was evaluated.
[0113] ◎ : Decomposed in 4 hours or less
[0114] ○ : Decomposed over 4 hours or more but less than 10 hours
[0115] × : Not decomposed for 10 hours or having decomposition residue
[0116] The abbreviations used in the examples and comparative examples are as follows.
[0117] [2-Sensory Epoxy Resin]
[0118] A1: 1,4-Cyclohexanedimethanoldiglycidyl ether (Manufactured by Nittetsu Chemical & Materials Co., Ltd., ZX-1658GS, epoxy equivalent 132)
[0119] [Chemical Formula 8]
[0120]
[0121] A2: Isosorbide diglycidyl ether (compound obtained in Synthesis Example 1, epoxy equivalent 157)
[0122] [Chemical Formula 9]
[0123]
[0124] A3: Bisphenol A type liquid epoxy resin (Manufactured by Nittetsu Chemical & Material Co., Ltd., YD-128, epoxy equivalent 186)
[0125] [Chemical Formula 10]
[0126]
[0127] A4: Bisphenol A type liquid epoxy resin (manufactured by Nittetsu Chemical & Materials Co., Ltd., mixture of YD-011 and YD-128 (mixing ratio: YD-011:YD-128 = 90:10), epoxy equivalent 420)
[0128] [Chemical Formula 11]
[0129]
[0130] [Carbohydrate ester compounds]
[0131] B1: Diphenyl carbonate (manufactured by Tokyo Kasei Kogyo Co., Ltd., molecular weight 214, active equivalent 107)
[0132] [Chemical Formula 12]
[0133]
[0134] [Hardening agent]
[0135] C1: 4-Methylhexahydrophthalic anhydride (Manufactured by Shin-Nihon Rica Co., Ltd., Ricaside MH-T, active hydrogen equivalent 168)
[0136] [Chemical Formula 13]
[0137]
[0138] [catalyst]
[0139] D1: 4-Dimethylaminopyridine (Manufactured by Fujifilm Wako Junyaku Co., Ltd.)
[0140] [Chemical Formula 14]
[0141]
[0142] D2: 2-ethyl-4-methylimidazole (manufactured by Shikoku Kasei Kogyo Co., Ltd., 2E4MZ)
[0143] [Chemical Formula 15]
[0144]
[0145] Synthesis Example 1
[0146] 100 parts of isosorbide (manufactured by Tokyo Kasei Kogyo Co., Ltd.) and 633 parts of epichlorohydrin were injected into a glass separable flask equipped with a stirrer, thermometer, nitrogen inlet tube, reflux condenser with an oil-water separator, and a vacuum device, and the temperature was raised to 63°C while stirring under a nitrogen atmosphere. 11 parts of a 50% sodium hydroxide aqueous solution were quantitatively injected over 2 hours. Next, while maintaining the temperature inside the reaction system at 65°C, the epichlorohydrin was refluxed under gradually reduced pressure. 109 parts of a 50% sodium hydroxide aqueous solution were continuously added dropwise over 2 hours. During this time, the degree of reduced pressure was 120 Torr, and the azeotrope of water and epichlorohydrin was separated into two layers in an oil-water separator; the epichlorohydrin in the lower layer was returned to the system, and the water in the upper layer was removed from the system. After the reaction, the pressure and temperature were gradually reduced and the epichlorohydrin was distilled and removed until it finally reached 150 °C and 5 Torr. Then, the reaction system was returned to atmospheric pressure, 300 parts of toluene were added to dissolve it, and 500 parts of water were added to separate and remove the byproduct salt. After that, washing was repeated with 300 parts of water until the washing water became neutral. From this solution, toluene was removed by heating to 150 °C under a reduced pressure of 5 Torr to obtain a liquid epoxy resin (A2). The obtained liquid epoxy resin (A2) had an epoxy equivalent of 157 g / eq.
[0147] Example 1
[0148] In a four-necked glass separable flask equipped with a stirring device, a thermometer, a cooling tube, and a nitrogen gas introduction device, 100 parts of 1,4-cyclohexanedimethanoldiglycidyl ether (A1) as an epoxy resin and 44 parts of diphenyl carbonate (B1) as a carbonate ester compound were injected at room temperature. The temperature was raised to 125°C while stirring with nitrogen gas flow, 0.007 parts of catalyst (D1) were added, and the temperature was raised to 145°C. The reaction was carried out at the same temperature until there was no change in the epoxy equivalent, thereby obtaining a modified epoxy resin (R1). "Carbonate concentration" in Table 1 indicates the molar amount of diphenyl carbonate per 100 g of solid content after injection. For the obtained modified epoxy resin (R1), Mw, epoxy equivalent, and melt viscosity were measured. The results are shown in Table 1. Figure 1 shows a GPC chart, and Figure 2 shows an IR chart.
[0149] Examples 2 to 12, Comparative Examples 1 and 2
[0150] According to the injection amount (parts) of each raw material shown in Table 1, the same operation as in Example 1 was performed to obtain resins related to Examples 2 to 12 (R2 to R12) and resins related to Comparative Examples 1 and 2 (HR1, HR2). The epoxy equivalents and melt viscosities of R2 to R12 and HR1, HR2 were measured. The results are shown in Table 1.
[0151]
[0152] Example 13
[0153] 100 parts of the modified epoxy resin (R1) obtained in Example 1 as the epoxy resin, 40 parts of 4-methylhexahydrophthalic anhydride (C1) as the curing agent, and 0.2 parts of 2-ethyl-4-methylimidazole (D2) as the curing accelerator were mixed and stirred while vacuum degassing for 5 minutes using a vacuum planetary mixer for a rotational and orbital laboratory to obtain a liquid resin composition. Next, this liquid resin composition was poured into a 2 mm thick mold that had been preheated to 100°C, and then placed in a hot air oven to perform heat curing at 100°C for 2 hours and at 150°C for 5 hours to obtain a cured product. The bending modulus and decomposition time were measured by cutting the cured product obtained to a size suitable for each measurement. The results are shown in Table 2.
[0154] Examples 14–24, Comparative Examples 3, 4
[0155] According to the injection amount (parts) of each raw material shown in Table 2, the same operation as in Example 13 was performed to obtain the cured products related to Examples 14 to 24 and the cured products related to Comparative Examples 3 and 4. The bending modulus and decomposition time were measured by cutting the cured products obtained to a size suitable for each measurement. The results are shown in Table 2.
[0156]
[0157] As can be seen from Table 1, the modified epoxy resins of the present invention shown in Examples 1 to 12 have low viscosity while maintaining or increasing the carbonate concentration related to the decomposition time. In addition, as can be seen from Table 2, the cured modified epoxy resins of the present invention shown in Examples 13 to 24 have excellent mechanical properties and decomposition properties.
Claims
Claim 1 A modified epoxy resin characterized by being represented by the following general formula (1). Here, X is a monovalent group represented by the above formula (2-1) or the above formula (2-2), and the above formula (2-1) and the above formula (2-2) may be mixed within one molecule. Y is a divalent group and has at least a dicyclic hydrocarbon group that may have heteroatoms. n 1 n is the average value of the number of repetitions, and is between 0 and 500 inclusive. 1 If this is 0, X has at least the group represented by Equation (2-2). n 2 is the average value of the number of repetitions, and is between 0 and 6 inclusive. Claim 2 A modified epoxy resin according to claim 1, wherein Y is a divalent group and has at least 10 mass% of a carbon alicyclic hydrocarbon group having 1 to 15 carbon atoms that may have an oxygen atom. Claim 3 In claim 2, Y is a divalent group, and the modified epoxy resin has at least 10 mass% of a divalent group represented by the following formula (3-1) and / or the following formula (3-2). Claim 4 A resin composition characterized by comprising a modified epoxy resin and a curing agent as described in claim 1. Claim 5 A cured product formed by curing the resin composition described in claim 4. Claim 6 A prepreg comprising a resin composition or its semi-material described in claim 4 and a fibrous substrate. Claim 7 A resin sheet comprising a resin composition or a semi-material described in claim 4 and a supporting film. Claim 8 A laminated plate formed by laminating the prepreg described in claim 6 and / or the resin sheet described in claim 7. Claim 9 A resin composition for fiber-reinforced composite materials characterized by being formed by impregnating a reinforcing fiber with the resin composition described in claim 4. Claim 10 A fiber-reinforced composite material obtained from a resin composition for fiber-reinforced composite materials described in claim 9. Claim 11 A method for manufacturing a modified epoxy resin according to claim 1, characterized by reacting a difunctional epoxy resin represented by the following general formula (4) with a diphenyl carbonate represented by the following formula (5). Here, Y, n 2 is the same meaning as general formula (1). G is the 1-value group represented by the above formula (2-1). Claim 12 A method for decomposing a cured material or a fiber-reinforced composite material, characterized by reacting the cured material described in claim 5 or the fiber-reinforced composite material described in claim 10 with a primary amine. Claim 13 A method for decomposing a laminate characterized by reacting the laminate described in claim 8 with a primary amine.
